Improved dispenser for use in preparing prereduced, anaerobically sterilized medium. - Fulghum, R S (1977)
An improved, all glass, gravity-fed quantitative device for dispensing media during preparation of prereduced, anaerobically sterilized media with minimal loss due to oxidation of media is described.